PENGELOLAAN SUMBERDAYA GURU ENSINO SECUNDARIO GERAL GUNA MENINGKATKAN MUTU PENDIDIKAN - Clarita Sariyanti Tavares; nasharuddin mas (JIM (Jurnal Ilmu Manajemen), 2020)
ABSTRACT  This article aims to explore the process of managing teacher resources and the supporting and inhibiting factors in improving the quality of education. The approach of this research is an descritive study on ensino secundario general teachers of East Leste. The informants consisted of the principal, vice principal, homeroom teacher, subject teachers, alumni, and the administration section. Collecting data using interviews, observation and documentation. Data analysis used Miles and Huberman's model. The findings of the study indicate that the management of teacher resources has regulations that are regulated by the school and the education office. The supporting factors are in order to improve the quality of education by establishing good relationships between teachers and students and being able to work together with parents of students. Meanwhile, the inhibiting factor relates language, an unfavorable environment and depth in implementing teacher career development programs. Keywords: Teacher Resource Management, Education Quality, Interpretive Studies, Miles and Huberman ModelABSTRAK  Artikel ini bertujuan untuk mengekplorasi proses pengelolaan sumber daya guru beserta faktor-faktor pendukung dan penghambat dalam meningkatkan mutu pendidikan. Pendekatan penelitian ini adalah studi deskriptif pada guru ensino secundario geral Timur Leste. Informan terdiri dari kepala sekolah, wakil kepala sekolah, wali kelas, guru mata pelajaran, alumni, dan bagian administrasi. Pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Serta analisis data menggunakan model Miles dan Huberman. Temuan penelitian menunjukkan bahwa pengelolaan sumber daya guru memiliki regulasi yang telah diatur oleh pihak sekolah dan pihak dinas pendidikan. Pada faktor pendukung guna meningkatkan mutu pendidikan dengan menjalin hubungan baik antara guru dan murid dan dapat bekerja sama dengan orang tua siswa. Sedangkan, faktor penghambatnya kendala bahasa, lingkungan yang kurang kondisif dan kedala dalam implementasi program pengembangan karir guru. Kata Kunci: Pengelolaan Sumberdaya Guru, Mutu Pendidikan, Studi Interpretatif, Model Miles dan Huberman